Preferensi UKM Kuliner dalam Pengolahan Sertifikasi Halal Secara Online di Kota Pekanbaru - Sidabalok, Supriani; Misdawita, Misdawita; Zamaya, Yelly; Mayes, Anthony (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2024)
This research aims to determine the preferences that influence the decision of culinary SMEs in Pekanbaru City in processing halal certification online. Preference measurement is based on factors that influence individual perceptions in making decisions, namely ease, trust, benefits, and risk. The data collection method is a questionnaire with a Likert scale and data processing using binary logistic regression (logit regression). Based on data collection and analysis from 78 of culinary SMEs, the results showed that simultaneously all perception variables influenced culinary SMEs decisions to obtain halal certificates online. As for the individual test results, it showed that three perception factors, namely ease (X1), benefits (X3), and risk (X4) had a significant effect on culinary SMEs preferences for processing online halal certificates, while perceptions of trust (X2) had no significant effect. This is in accordance with the odds ratio value for each influential variable, namely 3.910 times, 2.593 times and 5.510 times for each variable. Perception of usefulness is the strongest factor influencing the decision of culinary SMEs in Pekanbaru City to process halal certification online.